Oil price shocks, global economic policy uncertainty, geopolitical risk, and stock price in Malaysia: Factor augmented VAR approach - Mohammad Enamul Hoque (Ekonomska Istraživanja, 2019)
This article examines the impacts of the geopolitical risk, global economic policy uncertainty, and oil price shocks on stock prices in Malaysia using factor augmented SVAR approach. The findings show that while geopolitical risk has no significant direct impacts on the overall stock market, its indirect impacts are significant and transmitted through the global economic policy uncertainty and oil shocks channels. Global economic policy uncertainty exerts negative effects on the overall stock market and its impacts are magnified by geopolitical risk. Oil related shocks exhibit asymmetric effects on both the aggregated and sectoral stock price. The impacts of oil demand shock on stock price are amplified by global economic uncertainty factor whereas oil supply shocks impacts are amplified by the geopolitical risk factor. At sectoral level, the impacts of all the global shocks vary across different sectors and time. The overall findings imply that global economic policy uncertainty and oil demand shock factors are systematic risk factors that can be employed to forecast stock market returns. The findings also provide implications for policymakers to regulate markets in maintaining financial stability and investors to react to future shocks in these global economic factors with regard to the risks and opportunities.